Development and Videographic Evaluation of a Vascular Access Simulation-Based Curriculum for Surgical and Medical Trainees - Alaska Pendleton, MD, MPH; Tiffany R. Bellomo, MD; Srihari K. Lella, MD; Kristen Jogerst, MD; Ada Stefanescu, MD, MSc; Douglas Drachman, MD; Nikolaos Zacharias, MD; Anahita Dua, MD, MBA, MSc (Annals of Surgery Open)
Background:. There is a paucity of data evaluating femoral arterial access training, despite significant morbidity/mortality associated with incorrect femoral arterial access. The aim of this study was to develop and evaluate a novel 2-component simulation-based curriculum to address a lack of standardized access training and identify the most frequent errors in access. Methods:. The femoral arterial access curriculum was developed through a multi-disciplinary collaboration and utilized in-person simulation sessions in conjunction with online and in-person didactic training. Access errors and curriculum efficacy were assessed using mixed-methodology evaluation of video recordings of trainee arterial access pre- and postcurriculum. All recordings were reviewed and scored by 2 blinded, independent investigators. Results:. Twenty-six participants completed the curriculum with pre- and postcurriculum recordings. Sixteen participants (62%) were in their first year of residency training. Fifteen participants (58%) belonged to general surgery residency, 9 (35%) to emergency medicine, 1 to vascular surgery, and 1 to interventional radiology residency programs. The global rating for the overall ability to obtain femoral arterial access under ultrasound guidance (0 = fail, 4 = excellent) improved following the curriculum (0.87 ± 0.15, 2.79 ± 1.26, P < 0.0001). Fourteen participants (54%) were unable to independently complete the procedure before training, compared to only 2 participants (8%) following the curriculum. Procedural completion time decreased from 7.14 ± 4.26 to 3.81 ± 2.53 minutes (P < 0.001). Most frequent errors, determined through qualitative analysis, included difficulty using the ultrasound and unsafe maneuvers. Conclusions:. Before the curriculum, there were significant frequent errors in junior resident femoral arterial access with major patient safety concerns. A novel simulation-based femoral arterial access curriculum resulted in improved procedural skills across all metrics.